Effect of Salinity Stress on Some Seed Germination Indices in Sour Orange (Citrus aurantium) - M. A. Shiri (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2011)
In order to study the effect of sodium chloride (NaCl), as a salinity stress factor, on sour orange seed germination indices, an experiment was conducted in a completely randomized design with 3 replica‌tions (each replication included 20 seeds) at the University of Guilan, in 2009. NaCl levels were 0, 7.8, 15.6 and 23.4 dS/m. The results showed that various levels of NaCl had significant effect on all the studied traits. Seed germination in 23.4 dS/m treatment started later than other treatments. The highest germination was in control and 7.8 dS/m NaCl treatments. The 15.6 and 23.4 dS/m NaCl treatments had the least germination percentage (85.7 and 46.9%, respectively). The highest germination index (length of germination period) was in 23.4 dS/m treatment followed by 15.6 and 7.8 dS/m and control with no significant difference. T50 was highest in 23.4 dS/m and lowest in control treatments. Mean daily germination, seed growth rate and seed vigor were highest in control treatment, with no significant difference with 7.8 dS/m treatment. Overall, it was found that germination of sour orange seeds is resistant to 7.8 dS/m NaCl, and they are able to germinate and grow in saline soils, as well.